2005
DOI: 10.3133/sir20055017
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of drainage-area ratio method used to estimate streamflow for the Red River of the North Basin, North Dakota and Minnesota

Abstract: The drainage-area ratio method commonly is used to estimate streamflow for sites where no streamflow data were collected. To evaluate the validity of the drainage-area ratio method and to determine if an improved method could be developed to estimate streamflow, a multiple-regression technique was used to determine if drainage area, main channel slope, and precipitation were significant variables for estimating streamflow in the Red River of the North Basin. A separate regression analysis was performed for str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 13 publications
0
51
0
Order By: Relevance
“…For example, Emerson et al (2005) and Asquith et al (2006) showed that more-advanced calibration of variants of the DAR method are promising, while Shu and Ouarda (2012) showed that the use of multiple index sites may be valuable. Furthermore, it may be possible to improve Step 2, regional characterization of streamflow records, to reduce both the bias and variance of resulting flow estimates at the ungauged site.…”
Section: Conclusion and Recommendationsmentioning
confidence: 97%
See 2 more Smart Citations
“…For example, Emerson et al (2005) and Asquith et al (2006) showed that more-advanced calibration of variants of the DAR method are promising, while Shu and Ouarda (2012) showed that the use of multiple index sites may be valuable. Furthermore, it may be possible to improve Step 2, regional characterization of streamflow records, to reduce both the bias and variance of resulting flow estimates at the ungauged site.…”
Section: Conclusion and Recommendationsmentioning
confidence: 97%
“…Instead, the most common approach is used for Step 1, that of choosing the nearest gauge to a site of interest as the index gauge. Though this method is suggested by the work of Emerson et al (2005), Asquith et al (2006) and Mohamoud (2008), and many others, recent publications have found other, more promising criteria for selecting index gauges. For example, Archfield and Vogel (2010) found that the correlation between two streamflow records provides a promising metric for evaluation of hydrologic similarity between an index gauge and a site of interest.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The ratios of mean naturalized flows for specified periods in Eq. (1) were applied in the same manner that conventional drainage area ratios are applied routinely in many other studies (Emerson and Dressler, 2002;Emerson et al, 2005;Guenthner et al, 1990;Hirsch, 1979;Mohamoud, 2008). Mean flow ratios replace drainage area ratios.…”
Section: Distribution Of Naturalized Flow To Control Points With Missmentioning
confidence: 99%
“…These data were obtained from the Ebro Basin Authority (CHE) website. Discharge estimates in the other sites were performed by using discharge values at nearby stations and sub-basin total drainage areas as described by the Drainage-Area Ratio Method (Emerson et al, 2005).…”
Section: Samplingmentioning
confidence: 99%